2011
DOI: 10.1118/1.3662072
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided detection of clustered microcalcifications in digital breast tomosynthesis: A 3D approach

Abstract: Purpose: To design a computer-aided detection (CADe) system for clustered microcalcifications in reconstructed digital breast tomosynthesis (DBT) volumes and to perform a preliminary evaluation of the CADe system. Methods: IRB approval and informed consent were obtained in this study. A data set of two-view DBT of 72 breasts containing microcalcification clusters was collected from 72 subjects who were scheduled to undergo breast biopsy. Based on tissue sampling results, 17 cases had breast cancer and 55 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
2
44
0
2
Order By: Relevance
“…to 90% with false-positive rates of 0.65 to 1.55 per DBT volume (6,9,10). In the present study, we observed same case-based sensitivities [100% (31/31)] for malignant calcifications with a 0.52 false-positive mark rate per DBT volume, which is better than the results of previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…to 90% with false-positive rates of 0.65 to 1.55 per DBT volume (6,9,10). In the present study, we observed same case-based sensitivities [100% (31/31)] for malignant calcifications with a 0.52 false-positive mark rate per DBT volume, which is better than the results of previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…To overcome aforementioned problems, preprocessing is performed to enhance microcalcifications. In our work, SNR enhancement [3] and 3D Laplacian of Gaussian filtering was incorporated. 3D Laplacian of Gaussian filtering response…”
Section: Improvement Of Subtle Microcalcifications Detection In Dbt Smentioning
confidence: 99%
“…Sahiner et al [3] proposed a system for detecting clustered microcalcifications from 3D volumes in a 3D approach. In another study, Bernard et al [4] proposed a method for microcalcification detection from filtered back-projection reconstructed slices with a Mexican hat wavelet based enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salama et al [11] used iterative thresholding and adaptive region growing to detect microcalcification clusters while Sahiner et al [12] followed a 3D approach to achieve the same purpose through iterative thresholding and a 3D object growing method.…”
Section: Introductionmentioning
confidence: 99%